Evaluation of lightning-induced tropospheric ozone enhancements observed by ozone lidar and simulated by WRF/Chem. (August 2015) - Wang, Lihua; Follette-Cook, Melanie B.; Newchurch, M.J.; Pickering, Kenneth E.; Pour-Biazar, Arastoo; Kuang, Shi; Koshak, William; Peterson, Harold
Abstract: High spatial- and temporal-resolution ozone lidar profiles, in conjunction with ozonesonde and satellite observations, are well suited to characterize short-term ozone variations due to different physical and chemical processes, such as the impact of lightning-generated NOx (LNOx ) on tropospheric ozone. This work presents the hourly variation of tropospheric-ozone profiles measured by an ozone lidar at the University of Alabama in Huntsville, on July 14, 18, and 27, 2011. These ozone lidar data are compared with two WRF/Chem simulations, one with lightning NO (LNO) emissions and the other without. On July 14, 2011, the ozone lidar observed an ozone laminar structure with elevated ozone concentrations of 65∼80 ppbv below 2 km, low ozone (50∼65) ppbv between 2 and 5 km, and high ozone up to 165 ppbv between 5 and 12 km AGL. WRF/Chem simulations, in conjunction with backward trajectory analysis, suggest that lightning events occurring within upwind regions resulted in an ozone enhancement of 28 ppbv at 7.5 km AGL over Huntsville. On July 27, LNO emissions were transported to Huntsville from upwind and account for 75% of NOx and an 8.3 ppbv of ozone enhancement at ∼10 km; the model overestimates ozone between 2.5 and 5 km AGL. Highlights: Lidar measures ozone profiles at Huntsville, AL on July 14, 18 and 27, 2011. Lightning-NOx emission (LNOx) is estimated based on NLDN flash measurements. LNOx emission applies to WRF/Chem for simulating lightning influence. Lidar-measured ozone variation is compared to model. Upwind lightning resulted in ozone enhancements at Huntsville on July 14 and 27.